GAMBARAN SISWA/SIWSI SEKOLAH MENENGAH PERTAMA TERHADAP PERILAKU MEROKOK DI KOTAMADYA PEKANBARU - Dian Rahmi Yenti; Dedi Afandi (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTProblems in regard to smoking have not yet been solved up until now. One of the urgent problem is in junior high school, for it is the place to create and develop the next generation whom not only excell in academic-wise but health and environment oriented as well. Perception of this research is based upon students’ point of view toward smoking’s impact which is then interpretated according to their experiences and cognition. The students’s perspective on smoking habit is greatly influenced by their characteristic in school. This research was a descriptive study with cross-sectional approach. This study was done in July 2014 with 210 teachers ranging from 7 junior high schools as the respondents. The result showed 44 out of 210 respondents were found to be smokers.Key words: smoking, knowledge, perception.